2016
DOI: 10.5812/numonthly.34421
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy Suppresses Apoptosis and Promotes Renal Tubular Regeneration After Renal Ischemia/Reperfusion Injury in Rats

Abstract: Background:Renal ischemia/reperfusion (I/R) injury remains a major cause of acute kidney injury (AKI), in addition to I/R injury-induced tissue inflammation, necrosis and apoptosis. Hyperbaric oxygen therapy (HBO) is defined as a treatment in which a patient is intermittently exposed to 100% oxygen pressurized to a pressure above sea level (> 2.0 atmospheres absolute (ATA), 1.0 ATA = 760 mmHg). It has been used in a number of medical conditions with a proven efficacy in a limited number of disorders. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…In animal models, HBO has been shown to offer protection from AKI caused by factors such as renal ischemia/reperfusion, rhabdomyolysis‐induced myoglobin and cisplatin‐induced tubular necrosis . It was shown that HBO could induce anti‐oxidant enzyme activity and suppress lipid peroxidation under oxidative stress in AKI .…”
Section: Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, HBO has been shown to offer protection from AKI caused by factors such as renal ischemia/reperfusion, rhabdomyolysis‐induced myoglobin and cisplatin‐induced tubular necrosis . It was shown that HBO could induce anti‐oxidant enzyme activity and suppress lipid peroxidation under oxidative stress in AKI .…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…It was shown that HBO could induce anti‐oxidant enzyme activity and suppress lipid peroxidation under oxidative stress in AKI . Furthermore, HBO was also shown to exert tubular cell regeneration through the inhibition of apoptosis . Although there is scant evidence regarding the effect of HBO on AKI in humans, the application of HBO therapy in the human kidney is expected in the near future.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Moreover, the aberrant apoptosis of renal cells, such as tubular cells, due to elevated oxidative stress and enhanced mitochondrial pathway activity has been demonstrated to occur during the pathogenesis of renal iri (8). Several therapeutic reagents and methods that inhibit renal cell apoptosis have demonstrated promising potential as novel treatments for renal iri in animal models, which require further validation; these include hyperbaric oxygen therapy, hydrogen-rich saline and hypothermic machine perfusion (9)(10)(11). investigating the molecular mechanisms that underlie the pharmacological effects of anti-iri drugs may enable the development and clinical application of novel therapies for iri.…”
Section: Introductionmentioning
confidence: 99%
“…This therapy enhances the dissolved oxygen concentration in arterial blood and restores the diffusion of oxygen into poorly perfused tissues ( 6 , 7 ). Animal studies have shown that HBO therapy attenuates ischemia reperfusion-induced tissue injury by abating oxidative stress, suppressing inflammation, increasing nitric oxide formation and preventing apoptosis ( 7 - 9 ).…”
Section: Introductionmentioning
confidence: 99%